2016
DOI: 10.1016/j.ijggc.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the corrosion of CO2-loaded 2-amino-2-methyl-1-propanol solutions assisted by thermodynamic modeling

Abstract: Corrosion of A106 carbon steel in a naturally aerated 30 wt.% 2-amino-2-methyl-1-propanol-based solution (AMP, a sterically hindered primary amine) with 0.43 mol CO2 /mol AMP was evaluated at 80°C. Substantial decrease in corrosion rate, i.e., over two orders of magnitude, was observed over the initial 70 h, which is the result of formation of a protective FeCO 3 layer followed by passivation of the A106 surface. Mechanisms for formation of these protective layers are discussed with comparison to corrosion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The addition of AMP in conjunction with MEA aims to explore potential synergistic effects and evaluate its effectiveness in enhancing corrosion resistance, as suggested by previous studies. 18,[23][24][25] Long-term immersion corrosion experiments and electrochemical tests, including polarization curves and electrochemical impedance spectroscopy (EIS) measurements, were conducted to analyze corrosion rates, corrosion currents, and voltages for both materials. Additionally, inductively coupled plasma-optical emission spectroscopy (ICP-OES) and anion chromatography were used to test the concentration levels of Fe ions and HSS in the liquid phase absorbent, respectively, and the accumulation of degradation products under different conditions was analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of AMP in conjunction with MEA aims to explore potential synergistic effects and evaluate its effectiveness in enhancing corrosion resistance, as suggested by previous studies. 18,[23][24][25] Long-term immersion corrosion experiments and electrochemical tests, including polarization curves and electrochemical impedance spectroscopy (EIS) measurements, were conducted to analyze corrosion rates, corrosion currents, and voltages for both materials. Additionally, inductively coupled plasma-optical emission spectroscopy (ICP-OES) and anion chromatography were used to test the concentration levels of Fe ions and HSS in the liquid phase absorbent, respectively, and the accumulation of degradation products under different conditions was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…MEA is one of the most commonly employed amines in industrial CO 2 capture processes, making it a relevant choice for this study. The addition of AMP in conjunction with MEA aims to explore potential synergistic effects and evaluate its effectiveness in enhancing corrosion resistance, as suggested by previous studies 18,23–25 . Long‐term immersion corrosion experiments and electrochemical tests, including polarization curves and electrochemical impedance spectroscopy (EIS) measurements, were conducted to analyze corrosion rates, corrosion currents, and voltages for both materials.…”
Section: Introductionmentioning
confidence: 99%
“…AMP can be prone to degradation at high temperatures, despite its perception as generally being resistant to degradation. , Previous studies have shown that AMP can form a carbamate (AMPCOO – ) with CO 2 leading to thermal degradation with a similar pathway to that of MEA. , The thermal degradation rate of AMP to its main degradation product, 4,4-dimethyl-1,3-oxazolidin-2-one (DMOZD), was investigated in detail by considering an apparent reaction rate and pseudo-mechanistic approach. , The previous work introduced an inclusive apparent power-law AMP and CO 2 concentration-dependent reaction rate for AMP degradation to DMOZD in a broad range of AMP and CO 2 concentrations and system temperature. In the current study, the previous rate equation and parameters introduced for the AMP degradation rate in its CO 2 aqueous solutions are considered, along with the effect of the second chemical component in the reaction rate.…”
Section: Introductionmentioning
confidence: 99%